A Rare Case of an Irreducible Patella Dislocation - Dimitri E. Delagrammaticas; Scott D. Cordes (Case Reports in Medicine)
Reports of irreducible patellar dislocations are exceedingly sparse throughout the literature. Obvious radiographic or physical exam findings including fracture or inversion of the patella are often present to explain the block to reduction. Not described previously in the literature is the instance of an irreducible patella dislocation in the setting of innocuous appearing injury imaging. We present a case of a healthy thirty-two-year-old female who sustained an irreducible lateral patella dislocation while participating in a dance aerobics class. Closed means of reduction were unsuccessful, necessitating open reduction. Intraoperative findings suggest incarceration of a nondisplaced fracture and a chondral defect as the block to reduction. Following open reduction, the patient has had no further episodes of pain or instability related to the patella at one-year follow-up. Irreducible patellar dislocations are exceedingly rare injuries, where associated osseous or chondral lesions may necessitate open reduction despite innocuous appearing initial imaging. A high index of suspicion to proceed with open reduction may limit repeated attempts at closed reduction and further injury.